2018
DOI: 10.1097/scs.0000000000005047
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Spontaneous Closure and Paper Patching in Traumatic Tympanic Membrane Perforations

Abstract: The authors aim to analyze the effects of oral antibiotic treatment for traumatic tympanic membrane perforations and to compare the outcomes of patients with traumatic tympanic membrane perforation after paper-patching procedure and spontaneous healing. In this study, 80 patients with traumatic tympanic membrane perforation diagnosed in the otorhinolaryngology emergency department and outpatient clinic from March 2010 to January 2015 were retrospectively reviewed. If the patient is diagnosed at fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“…In two studies, the use of platelet‐derived growth factors with paper patching produced equivalent closure rates and hearing outcomes as compared to paper patch alone 15,29 . Furthermore, eight studies found higher closure rates in patients treated with paper patch (91.6%) than patients being observed for spontaneous closure (78.8%, P < .001) 14,21,23,25,31–34 . Reported outcomes of spontaneous closure consistently showed a longer duration for complete TM healing but similar postoperative audiometric outcomes when compared to paper‐patch grafting 14,21,25 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In two studies, the use of platelet‐derived growth factors with paper patching produced equivalent closure rates and hearing outcomes as compared to paper patch alone 15,29 . Furthermore, eight studies found higher closure rates in patients treated with paper patch (91.6%) than patients being observed for spontaneous closure (78.8%, P < .001) 14,21,23,25,31–34 . Reported outcomes of spontaneous closure consistently showed a longer duration for complete TM healing but similar postoperative audiometric outcomes when compared to paper‐patch grafting 14,21,25 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies reported outcomes of paper patches for repair of TM perforations 13–34 . Several different types of paper were utilized, including rice paper, cigarette paper, and paper patch (not otherwise specified).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations